Analisis Faktor Kualitas Pelayanan di Kelurahan Jatikarya Kecamatan Jatisampurna Kota Bekasi - Mary Ismowati; Sulatifah Sulatifah (Institut Ilmu Sosial dan Manajemen STIAMI, 2019)
There are still public complaints about the quality of services provided by the Jatikarya District Office and this is interesting to study to find out more about what factors in service quality are influential and what are the dominant factors in service quality in Jatikarya Village, Jatisampurna District, Bekasi City.This research uses a quantitative approach with factor analysis techniques. A sample of 96 respondents from the Jatikarya urban village community who had and were receiving services in the kelurahan. Questionnaire based on 5 dimensions namely tangibles, responsibility, responsiveness, empathy and assurance with 34 indicators. From the results of the study, it was found that 9 (nine) factors had an effect on the quality of service in Jatikarya Village, Bekasi City. Factors Officer preparedness is the most dominant in influencing the quality of service in Jatikarya Village, Bekasi City with a variance of 33, 590%. The second factor to the tenth factor is not dominant compared to Factor 1 as having Factor 2 accuracy (8.857%), factor ability and knowledge of officers (7.863%), facility completeness factor (6.850%), service to residents (4.731%), factor friendliness (4,039%), information clarity factor (3,833%), officer neatness factor (3,531%), and officer patience factor (2,999%), but in order to achieve organizational goals and better service quality Factor 2 to Factor 9 also should not ignored.